Prevalence and survival patterns of patients with bone metastasis from common cancers in Thailand - Phanphaisarn A. (2017)
Background: Bone metastasis is a single condition but presents with various patterns and severities. Skeletalrelated events (SREs) deteriorate overall performance status and reduce quality of life. However, guidelines for early detection and management are limited. This study includes a survey of the prevalence of bone metastasis in cases with common cancers in Thailand as well as a focus on survival patterns and SREs. Materials and Methods: A retrospective cohort analysis was conducted using a database of the Chiang Mai Cancer Registry and the Musculoskeletal Tumor Registry of the OLARN Center, Chiang Mai University. The prevalence of bone metastasis from each type of primary cancer was noted and time-to-event analysis was performed to estimate cancer survival rates after bone metastasis. Results: There were 29,447 cases of the ten most common cancers in Thailand, accounting for 82.2% of the entire cancer registry entries during the study period. Among those cases, there were 2,263 with bone metastases, accounting for 7.68% of entries. Bone metastasis from lung, liver, breast, cervix and prostate are common in the Thai population, accounting for 83.4% of all positive cases. The median survival time of all was 6 months. Of the bone metastases, 48.9% required therapeutic intervention, including treatment of spinal cord and nerve root compression, pathological fractures, and bone pain. Conclusions: The frequency of the top five types of bone metastasis in Thailand were different from the frequencies in other countries, but corresponded to the relative prevalence of the cancers in Thailand and osteophilic properties of each cancer. The results of this study support the establishment of country specific guidelines for primary cancer identification with skeletal lesions of unknown origin. In addition, further clinical studies of the top five bone metastases should be performed to develop guidelines for optimal patient management during palliative care.